2009
DOI: 10.1093/cvr/cvp148
|View full text |Cite
|
Sign up to set email alerts
|

Targeted G-protein inhibition as a novel approach to decrease vagal atrial fibrillation by selective parasympathetic attenuation

Abstract: These results demonstrate the feasibility of using specific G(i)-protein inhibition to achieve selective parasympathetic denervation in the PLA, with a resulting change in vagal responsiveness across the entire LA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…After the completion of the terminal electrophysiological study, the heart was removed and the atria snap frozen as previously described by us 15,23 . The explanted left atrium (PLA/PVs and LAA) were subjected to the following analysis: Real-time PCR, Western Blot, Immunofluroscnece, Masson-Trichrome staining, Immunohistochemical analysis for macrophages and Protein oxidation (Carbonylation).…”
Section: Methodsmentioning
confidence: 99%
“…After the completion of the terminal electrophysiological study, the heart was removed and the atria snap frozen as previously described by us 15,23 . The explanted left atrium (PLA/PVs and LAA) were subjected to the following analysis: Real-time PCR, Western Blot, Immunofluroscnece, Masson-Trichrome staining, Immunohistochemical analysis for macrophages and Protein oxidation (Carbonylation).…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned previously, M2-receptor stimulation by the parasympathetic nervous system leads to activation of the I K-ACh through a G-protein coupled mechanism, leading to increased potassium current and atrial effective refractory period shortening that promotes initiation and maintenance of AF. Aistrup et al have shown in two studies that inhibition of G-protein signaling in the atrium can lead to attenuated parasympathetic effects in the atrium [45, 46]. In a proof of concept animal study, G-protein inhibitory peptides targeting the C-terminus of the Gα i/o subunit, the subunit associated with parasympathetic M2-receoptors, were used to inhibit parasympathetic signaling in the atrium [46].…”
Section: Modulation Of Autonomic Effects On Atrial Potassium Current mentioning
confidence: 99%
“…Aistrup et al have shown in two studies that inhibition of G-protein signaling in the atrium can lead to attenuated parasympathetic effects in the atrium [45, 46]. In a proof of concept animal study, G-protein inhibitory peptides targeting the C-terminus of the Gα i/o subunit, the subunit associated with parasympathetic M2-receoptors, were used to inhibit parasympathetic signaling in the atrium [46]. Peptides targeting the C-terminal portion of Gα i were selectively delivered to the PLA by direct injection into the myocardium with associated electroporation.…”
Section: Modulation Of Autonomic Effects On Atrial Potassium Current mentioning
confidence: 99%
See 1 more Smart Citation
“…Modifying the effect of various neurohumoral factors may also be effective. Targeted Gi protein inhibition, 50) as well as inhibitors of the acetylcholineactivated K + channel, 51,52) was reported to have curative effects against experimental atrial fibrillation. Certain antiarrhythmic drugs, such as pilsicainide, appear to have some selectivity towards the pulmonary vein myocardium probably due to the less negative resting membrane potential.…”
Section: Pharmacological Strategies Against Pulmonary Vein Automaticitymentioning
confidence: 99%